2016
DOI: 10.1002/uog.14836
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of intravenous nicardipine in severely pre‐eclamptic women with a hypertensive crisis

Abstract: Objective Nicardipine permits rapid control of blood pressure in women with severe pre-eclampsia (PE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…As recently reviewed, few trials have evaluated hemodynamic‐guided antihypertensive therapy in pregnant women 7. Similar to the non‐pregnant literature, antihypertensive therapy based on cardiac output and total peripheral resistance may be an effective therapeutic strategy to improve maternal blood pressure control 23, 26, 27, 28, 29. Hemodynamic‐guided antihypertensive therapy for pregnant women presenting with any type of hypertension significantly reduced the rates of severe maternal hypertension from 18% to 3.5%, when compared with standard care 30.…”
Section: Discussionmentioning
confidence: 98%
“…As recently reviewed, few trials have evaluated hemodynamic‐guided antihypertensive therapy in pregnant women 7. Similar to the non‐pregnant literature, antihypertensive therapy based on cardiac output and total peripheral resistance may be an effective therapeutic strategy to improve maternal blood pressure control 23, 26, 27, 28, 29. Hemodynamic‐guided antihypertensive therapy for pregnant women presenting with any type of hypertension significantly reduced the rates of severe maternal hypertension from 18% to 3.5%, when compared with standard care 30.…”
Section: Discussionmentioning
confidence: 98%
“…It is considered beneficial to screen pregnant women at higher risk of heart failure before echocardiography using biomarkers, such as brain natriuretic peptide (BNP)/NT-proBNP and troponin I. Elevated levels of both troponin I and NT-proBNP are seen in patients with heart failure caused by peripartum cardiomyopathy,9 10 and high-sensitivity troponin T retains prognostic value in patients with chronic heart failure 11–13. However, there have been few studies regarding the associations between biomarker levels and echocardiography findings in pregnancy 14–17…”
Section: Introductionmentioning
confidence: 99%
“…Maternal CO is an important hemodynamic parameter that is subjected to substantial changes in pregnancy. TTE using pulsed‐wave Doppler ultrasound in the LVOT position is commonly used for CO measurement. Nevertheless, our systematic review revealed only three validation studies, including our own prospective study, of limited size, comparing TTE with the clinical gold standard.…”
Section: Discussionmentioning
confidence: 97%
“…Pregnancy imposes a substantial challenge on the maternal cardiovascular system. Complications such as pre‐eclampsia, cardiac disease, sepsis, hemorrhage and pulmonary embolism, which account for the majority of severe maternal morbidity and mortality, are characterized by profound hemodynamic disturbances. Maternal pulse rate and blood pressure are easily obtained and are often used alone as indirect surrogates of maternal cardiovascular function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation